2019
DOI: 10.3390/cells8050382
|View full text |Cite
|
Sign up to set email alerts
|

RAC1 Takes the Lead in Solid Tumors

Abstract: Three GTPases, RAC, RHO, and Cdc42, play essential roles in coordinating many cellular functions during embryonic development, both in healthy cells and in disease conditions like cancers. We have presented patterns of distribution of the frequency of RAC1-alteration(s) in cancers as obtained from cBioPortal. With this background data, we have interrogated the various functions of RAC1 in tumors, including proliferation, metastasis-associated phenotypes, and drug-resistance with a special emphasis on solid tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 103 publications
(115 reference statements)
1
76
0
Order By: Relevance
“…In cancer, Rac1 and Cdc42 are mutated, overexpressed and (or) hyperactivated. Hyperactivation of Rac and Cdc42 is primarily due to signaling via oncogenic upstream receptors, which in turn stimulate GEF activity (Arias-Romero and Chernoff, 2013; Kazanietz and Caloca, 2017;Maldonado and Dharmawardhane, 2018;De et al, 2019). However, GEFs themselves can become oncogenic by mutation or dysregulated expression ( Table 1).…”
Section: Type Of Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In cancer, Rac1 and Cdc42 are mutated, overexpressed and (or) hyperactivated. Hyperactivation of Rac and Cdc42 is primarily due to signaling via oncogenic upstream receptors, which in turn stimulate GEF activity (Arias-Romero and Chernoff, 2013; Kazanietz and Caloca, 2017;Maldonado and Dharmawardhane, 2018;De et al, 2019). However, GEFs themselves can become oncogenic by mutation or dysregulated expression ( Table 1).…”
Section: Type Of Cancermentioning
confidence: 99%
“…These receptors include RTKs, GPCRs, and integrins, which signal to other oncogenes such as PI3-K and Ras that can in turn activate Rac/Cdc42 GEFs, which themselves can be oncogenic (Figure 1). Therefore, upregulated Rac and Cdc42 can drive malignant signaling during acquisition of resistance to cancer therapies targeting cell surface receptors, by acting downstream of therapy resistance mechanisms such as Ras/MAPK and PI3-K/mTOR signaling (Baker et al, 2014;Cardama et al, 2018;Maldonado and Dharmawardhane, 2018;De et al, 2019).…”
Section: Rac/cdc42 Inhibitors In Therapy Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Rac1 is a multifunctional protein and regulate several cellular responses by regulating downstream effectors beside its role in scaffolding protein. It is found that Rac1 plays a crucial role in progression of cancers [25]. QPCR analysis indicates that Rac1 significantly downregulate after silibinin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the Naive group, the alveolar septum of the IR group at each time points was signi cantly thickened and the alveolar in ltrated with in ammatory cells ( Figure 1A-B), the proportion of collagen bers increased signi cantly from the 1 st week to the 12 th week ( Figure 1C-D), indicating that pulmonary in ammation and brosis was induced by IR. Intraperitoneal injection of NSC23766, an inhibitor of Rac1 14 , could signi cantly alleviate RILI both in the Low dose (4mg/kg) and the High dose (8mg/kg) groups, manifested as reduction in the thickening of the alveolar septum ( Figure 1A-B) and decrease in collagen ber proportion ( Figure 1C-D). Besides, the IR-induced up-regulation of Vimentin, γ-H 2 AX and TGF-β, which were important indicators of epithelial-mesenchymal transition (EMT) 15 , DNA damage and IR-induced injury, were also inhibited by NSC23766 treatment ( Figure 1E-F, Supplemental material, S1A-D).…”
Section: Rili Was Alleviated By Rac1 Inhibitionmentioning
confidence: 99%